Ma‘ānī Asmā’ Allāh al-Ḥusnā Ḥāl al-Iqtirān wa Ḥāl al-Ifrāḍ fī Khawātīm Ba‘ḍi Āyāt al-Qur’ān: Dirāsah Waṣfiyyah Taṭbiqiyyah: The Meanings of the Names of Allah in Case of Isolation and in the State of Combination in some Verses of the Qur’an: A Descriptive and Empirical Study - Ahmed Bello, Nuruddeen; Samaila, Ali (Jurnal Usuluddin, 2021)
The Quran is the fundamental source by which a person knows his Creator through the knowledge of the names of Allah and His attributes, which represents the subject of the unification of Allah and affects the faith of a Muslim, train his soul and conscience and refine his behavior. Thorough examination of the names and attributes of Allah in the Qur’an reveals that both the names and attributes can be found in either of the two instances: in a joint form or in isolation to show that in both cases they carry different meanings, so the study aimed at explaining the names and attributes of Allah, in both of the two instances in some verses of the Quran. The study followed the descriptive and empirical methods. The paper found that the names and attributes of Allah are tawqifiyyah,(Divine), there is no room for personal reasoning, and that the names and attributes of Allah signify perfect and sublime qualities, It was also discovered by the study that the name of (Allah) Al-‘Azīz (The Almighty) was associated with wisdom (Hikmah), the name of (Allah) Al-Laṭīf (The Gentle) with mercy (Rahmah) and the name of Al-‘Afuw (The forgiver) with power and ability (Qudrah). Based on this, the more a person knows Allah the more he reveres Him and follow His commandments. The research finally recommends that to guard the behaviour of a Muslim society, people need to learn the meanings of names and attributes of their Creator.